Regulatory Challenges of Integrating Psychedelics into Mental Health Sector - Kerem Kemal Soylemez; Emma Marie de Boo; Joanne Lusher (Psychoactives)
Psychedelic substances have recently emerged as a promising method for treating mental health conditions, despite a history of stigmatization and restriction in use. The present review synthesizes existing literature on the therapeutic potential of psychedelics such as LSD, psilocybin, and MDMA in addressing specific mental health conditions like depression, anxiety, and addiction. On reviewing the existing literature, it became apparent that when administered in controlled settings with psychological support, psychedelics can induce profound psychological insights, leading to long-lasting and positive changes in mood, cognition, and behaviour. This review discusses the ethical, social, and regulatory challenges linked to using psychedelics within the mental health sector across different countries, and how these might influence societal beliefs towards their efficacy and use. Further research would be beneficial for eliciting a deeper understanding of the use of psychedelics in the field of mental health, leading to the development of standardized administration protocols and a thorough appreciation of societal implications and long-term outcomes. This review discusses the potential for psychedelics to revolutionize mental health treatment while underlining the urgent need for rigorous scientific inquiry on this topic and the ethical considerations surrounding the use of psychedelics for therapeutic purposes.